The Effect of Non Freeze-dried Hydrogel-CHA on Fibroblast Proliferation - Wahyudi, Ivan A.; Nurwadji, Lea M. (UI Scholars Hub, 2014)
Bone damage can be caused by variety of surgical procedures. Bone reconstruction has been developed lately is tissue engineering techniques. One of materials that proved to be effective as a scaffold in tissue engineering is a hydrogel. The addition of carbonate apatite (CHA) will produce a hydrogel-CHA material which is believed to improve the mechanical properties and biological similarities with the original bone. Scaffold is considered an important aspect in the field of tissue engineering, because it’s ability to mimic extracellular matrix of the damaged tissue. Fibroblasts are mesenchymal cells that can be readily cultured in the laboratory and play a significant role in epithelial-mesenchymal interactions, secreting various growth factors and cytokines. On certain condition, Fibroblast will differentiate into bone-forming cells, osteoblasts. Objective: to determine the effect of non freezedried hydrogels - CHA on the number of fibroblasts. Methods: In the treatment groups (hydrogel and hydrogelCHA group), the static seeding, where cells and scaffolds were simply brought into contact, was performed. The other group contained only cells and growth media. Cells were seeded at a density of 2x104 cells/ml in a 96-well plate. Number of fibroblasts cell in each group was observed by light microscopy and quantitified by MTT assay on days 1, 2 and 3 post-application. Results: Proliferation of fibroblasts increased significantly on day 3rd after application of non freeze-dried hydrogel - CHA (p< 0.05). Conclusion: Application of non freeze-dried hydrogel - CHA may induce fibroblasts proliferation.